Analisis Kadar Protein Tepung Telur Ikan Sapu-Sapu sebagai Sumber Bahan Pakan Ikan dengan Metode Spektrofotometri UV-Vis - Andi Masriah; Muhamad Dwi Cahya; Vina Nur Nadiro; Supriyadi Supriyadi; Revaninna Putri Hardiyanto; Adam Ashil Ramadhan (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2025)
This study aims to analyze the protein content of suckermouth catfish (Pterygoplichthys sp.) egg meal and to evaluate its potential as a fish feed ingredient. Egg meal samples were analyzed using Uv-Vis spectrophotometry with a standard albumin curve approach using linear regression. The analysis showed that the protein content of suckermouth catfish egg flour ranged from 35 to 37%. This value indicates a fairly high protein content, suggesting its potential as an additional protein source in fish feed formulations. In addition, suckermouth catfish are an invasive species that negatively impacts aquatic ecosystems. Therefore, utilizing its eggs as a feed raw material not only provides economic added value but also helps control the population of this invasive species. The use of sapu-sapu fish egg meal can be a sustainable and economical alternative for providing feed raw materials, especially to support fish growth in intensive aquaculture systems.